Salt Units of the Kribi-Campo Sub-Basin Revisited, Using Offshore 2D Seismic and Boreholes Data: Depositional Context and Petroleum Implications - Mike-Franck Mienlam Essi; Joseph Quentin Yene Atangana; Mbida Yem; Serge Edouard Angoua Biouele; Eun Young Lee (Proceedings)
This work re-examines the salt unit through the Kribi-Campo sub-basin on the southeast part of the Cameroon Atlantic Margin. The results obtained from borehole data analysis show the occurrence of an evaporitic unit, localized in the Kribi area. The well to seismic-tie analysis reveals that this unit is observed beneath the Top Albian Unconformity and between the Flooding and Maximum Flooding Surfaces. Two characteristics of the salt dome and salt strips are described. Their depositional context seems to be related to a significant sea-level drop induced by a margin uplift during the Aptian. Concerning the petroleum implications, the target units constitute the good potential of stratigraphic traps in the study area, due to the observation of flatspot indicators.